Чужой ребенок: [роман] / М. Трауб - Трауб Маша (Проза Маши Трауб, 2015)
Экземпляры: Архангельская биб-ка (20190116) / Инвентарный номер: 978z5z699z77779z2 / Цена: 257.80 / Сис.шифр: Р 2 / Авт.знак: Т 65 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6-44